SISTEM PARIWISATA MANCINGAN RICE TERRACE TAMPAKSIRING SEBAGAI DAYA TARIK WISATA BUATAN BERBASIS MASYARAKAT - I Nengah Alit Nuriawan; I Made Sukandana; Ni Kadek Ari Cahyani (UHN IGB Sugriwa Denpasar, 2024)
Mancingan Rice Terrace holds potential as a community-based artificial tourist attraction that supports sustainable tourism through a Community-Based Tourism (CBT) approach. This study aims to evaluate the tourism system at Mancingan Rice Terrace, focusing on the role of local communities in management, the development of artificial attractions, and tourism's economic, social, and environmental impacts. A qualitative-descriptive approach was employed to analyze community involvement in destination development and their contribution to tourism sustainability. The findings reveal that artificial attractions, such as trekking paths, photo spots, and agricultural education programs, have enhanced the site’s appeal and boosted local economic growth. Active community participation has not only created jobs but also preserved environmental sustainability. However, challenges such as inadequate promotion and infrastructure remain obstacles to further tourism development in Mancingan Rice Terrace. Recommendations for strengthening promotion, community training, and infrastructure improvements are proposed to ensure more effective and sustainable tourism management. This research provides insights into the importance of community collaboration in developing sustainable artificial tourist attractions.